Stereotactic Radiosurgery for Acromegaly: An International Multicenter Retrospective Cohort Study. Issue 3 (10th May 2018) - Ding, Dale; Mehta, Gautam U; Patibandla, Mohana Rao; Lee, Cheng-Chia; Liscak, Roman; Kano, Hideyuki; Pai, Fu-Yuan; Kosak, Mikulas; Sisterson, Nathaniel D; Martinez-Alvarez, Roberto; Martinez-Moreno, Nuria; Mathieu, David; et al.
Abstract: BACKGROUND: Stereotactic radiosurgery (SRS) is a treatment option for persistent or recurrent acromegaly secondary to a growth hormone secreting pituitary adenoma, but its efficacy is inadequately defined. OBJECTIVE: To assess, in a multicenter, retrospective cohort study, the outcomes of SRS for acromegaly and determine predictors. METHODS: We pooled and analyzed data from 10 participating institutions of the International Gamma Knife Research Foundation for patients with acromegaly who underwent SRS with endocrine follow-up of ≥6 mo. RESULTS: The study cohort comprised 371 patients with a mean endocrine follow-up of 79 mo. IGF-1 lowering medications were held in 56% of patients who were on pre-SRS medical therapy. The mean SRS treatment volume and margin dose were 3.0 cm 3 and 24.2 Gy, respectively. The actuarial rates of initial and durable endocrine remission at 10 yr were 69% and 59%, respectively. The mean time to durable remission after SRS was 38 mo. Biochemical relapse after initial remission occurred in 9%, with a mean time to recurrence of 17 mo. Cessation of IGF-1 lowering medication prior to SRS was the only independent predictor of durable remission ( P = .01). Adverse radiation effects included the development of ≥1 new endocrinopathy in 26% and ≥1 cranial neuropathy in 4%. CONCLUSION: SRS is a definitive treatment option for patients with persistent or recurrent acromegaly after surgical resection. There appears to be a statistical association between the cessation of IGF-1 lowering medications prior to SRS and durable remission.